2006
DOI: 10.1097/00000542-200605000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Infarct-remodeled Myocardium Is Receptive to Protection by Isoflurane Postconditioning

Abstract: Infarct-remodeled myocardium is receptive to protection by isoflurane postconditioning via protein kinase B/Akt signaling. This is the first time to demonstrate that anesthetic postconditioning retains its marked protection in diseased myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 49 publications
4
45
1
2
Order By: Relevance
“…Isoflurane administration can activate opioid and adenosine receptors and blockade of these G-protein-coupled receptors can abolish cardiac protection produced by isoflurane [30]. Volatile anesthetics affect several signaling pathways implicated in preconditioning, including Src tyrosine kinase (Src), the phosphatidylinositol-3-kinase(PI3K)/protein kinase B/glycogen synthase kinase 3 beta pathway [31], protein kinase C (PKC) [32,33], and mitogen-activated protein kinases (MAPK), including extracellular signal-regulated kinase 1 and 2 (ERK1/2) [34] and p38 MAPK [35]. In addition, volatile anesthetics modulate ATP-sensitive potassium channel activity [32,33], the generation of reactive oxygen species, and mitochondrial permeability transition pore opening [36].…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane administration can activate opioid and adenosine receptors and blockade of these G-protein-coupled receptors can abolish cardiac protection produced by isoflurane [30]. Volatile anesthetics affect several signaling pathways implicated in preconditioning, including Src tyrosine kinase (Src), the phosphatidylinositol-3-kinase(PI3K)/protein kinase B/glycogen synthase kinase 3 beta pathway [31], protein kinase C (PKC) [32,33], and mitogen-activated protein kinases (MAPK), including extracellular signal-regulated kinase 1 and 2 (ERK1/2) [34] and p38 MAPK [35]. In addition, volatile anesthetics modulate ATP-sensitive potassium channel activity [32,33], the generation of reactive oxygen species, and mitochondrial permeability transition pore opening [36].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] At the end of the experiments, hearts were frozen at Ϫ20°C for 2 h and subsequently cut into five cross-section slices. Heart slices were incubated in a 1% TTC in 0.1 M phosphate buffer solution (pH 7.4) at 37°C for 20 min, and fixed overnight in 10% formaldehyde.…”
Section: Determination Of Myocardial Infarction and Injurymentioning
confidence: 99%
“…[10][11][12] In brief, ligation of the LAD coronary artery was performed in penbarbital-anesthetized rats, which were orally intubated and mechanically ventilated. Left thoracotomy was performed by opening the fourth intercostal space.…”
mentioning
confidence: 99%
“…Our laboratory and others have demonstrated that the cardioprotective benefits of IPost are dependent on the activation of Akt and Erk1/2 at the immediate onset of myocardial reperfusion [213,214]. Subsequent studies have confirmed the role for Akt and Erk1/2 in the setting of IPost in both non-diseased animal hearts and diseased ones [215,216] as well as human atrial muscle [217]. Interestingly, obese mice have been reported to be resistant to IPost protection, and this finding was associated with insufficient activation of the RISK pathway in the hearts harvested from obese animals compared to control ones [218].…”
Section: Signal Transduction Pathwaysmentioning
confidence: 73%